1999
DOI: 10.1007/s10434-999-0562-x
|View full text |Cite
|
Sign up to set email alerts
|

Management of Extremity Recurrences After Complete Responses to Isolated Limb Perfusion in Patients With Melanoma

Abstract: Isolated extremity recurrences after CRs to ILP occurred in 35% of patients. Initially, these could be managed successfully by excision or repeat ILP for the majority of patients (92%). We recommend excision of small-volume recurrent disease, reserving repeat ILP for patients with increasing numbers of lesions or increasing rapidity of in-field recurrences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 13 publications
1
11
2
Order By: Relevance
“…In view of these results the treating surgeon may have tended to increase the drug dose slightly for repeat ILI in the hope of attaining an optimal result in this difficult to treat patient group. Although CR rates are lower, OR, duration of response and survival are comparable to those reported after repeat ILP for recurrent limb disease [7,59,60]. It can be concluded that a repeat ILI procedure can be of value if limb disease progresses or recurs after an initial ILI.…”
Section: Repeat Isolated Limb Infusionsupporting
confidence: 70%
“…In view of these results the treating surgeon may have tended to increase the drug dose slightly for repeat ILI in the hope of attaining an optimal result in this difficult to treat patient group. Although CR rates are lower, OR, duration of response and survival are comparable to those reported after repeat ILP for recurrent limb disease [7,59,60]. It can be concluded that a repeat ILI procedure can be of value if limb disease progresses or recurs after an initial ILI.…”
Section: Repeat Isolated Limb Infusionsupporting
confidence: 70%
“…11,12,22,23 The advantage of ILI compared with other local treatments is that the whole area at risk of recurrence is treated, with the possibility of eradicating microscopic disease that may be present in the affected limb. 33,34 The increased median duration of response after ILI and ILP…”
Section: Discussionmentioning
confidence: 99%
“…In 11 studies analyzing 544 hyperthermic ILPs, the median CR rate was 61.80% (range, 36.00%-89.00%) [14, 16 -19, 22, 25, 26, 29 -31]; 61.03% of the hyperthermic perfusions (n ϭ 332 perfusions) were applied with the double-agent melphalan plus TNF regimen [14,18,19,22,25,26,29,30]. The median CR rate to normothermic ILP, as shown in two studies analyzing 303 normothermic regimens with melphalan, was 47.00% (range, 42.00%-76.00%).…”
Section: Clinical Responsementioning
confidence: 99%
“…Valid data on the effectiveness of ILP in terms of clinical response were yielded by 20 studies analyzing 1,587 ILPs, reporting a median OR rate of 90.35% (range, 64.00%-100.00%) with a median CR rate of 58.20% (range, 25.00%-89.00%) [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] (Table 3).…”
Section: Clinical Responsementioning
confidence: 99%